Symbolic Ratification and Cultural Resistance: South Korea’s Dilemma in Implementing CEDAW (Convention on Elimination of All Forms of Discrimination Against Women) - MM, Imaniar Insy Savety Habibah (Department of International Relations, Hasanuddin University, 2026)
This article aims to examine the implementation of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) in South Korea, with particular attention to the influence of the country’s patriarchal cultural structure. It focuses on analyzing how and why patriarchal norms influence the implementation of CEDAW in South Korea. This article employs Cultural Theory as the analytical framework to explore how cultural values can affect the enforcement of global norms. It argues that the embedded norms and values within a state, in this case, South Korea, significantly hinder the effective implementation of international norms. Although South Korea has formally committed to implementing CEDAW and promoting women's rights and gender equality, the realization of these goals remains challenging due to the deeply entrenched patriarchal culture, which often marginalizes women’s roles in society. This article finds that the implementation of CEDAW is obstructed by the South Korean government’s reluctance to trigger domestic instability by imposing global norms that contradict prevailing cultural values. At the same time, the government faces international pressure to maintain its image as a committed actor for gender equality on the global stage.